Budaya Organisasi dan Motivasi terhadap Kinerja Karyawan PT. Telkom Indonesia Regional V Surabaya - Dea Aulia Permartasari (Jurnal Ilmu Manajemen, 2020)
The purpose of this study is to examine and analyze the influence of organizational culture and motivation on employee performance at PT. Telkom Indonesia Regional V Surabaya. Quantitative methods are used to obtain data by returning questionnaires that have been filled out by employees. In this study, the sample used was 80 people from a total population of 168 people. The sample is taken from each unit at PT. Telkom Indonesia Regional V Surabaya. Data analysis is Structural Equation Modeling (SEM) with PLS (Partial Least Square) approach using Smart PLS software. The results of this study indicate that the influence of organizational culture has a positive and significant effect on employee performance, and motivation has a positive and significant effect on employee performance.